Effects of salicylic acid, benzothiadiazole, and other commercial biostimulants on boosting faba bean (Vicia faba L.) tolerance against Orobanche spp - Amal Bouallegue; Faouzi Horchani; Siwar Thebti; Imen Trabelsi; Zayneb Kthiri; Moez Amri; Mohamed Kharrat; Zouhaier Abbes (PLoS ONE, 2025)
Broomrapes (Orobanche spp.) caused important agricultural problems reducing faba bean cultivated area and production in Tunisia. The effect of chemical tolerance inducers (Salicylic Acid SA and Benzothiadiazole BTH) and commercial biological tolerance inducers (Serenade, Trianum-P and Panoramix) on the induction of tolerance to O. foetida and O. crenata on faba bean was studied under field and controlled conditions experiments. These tolerance inducers were evaluated on the susceptible small seeded faba bean cv. Bachaar and applied as seeds’ pretreatment (seeds priming – coating). SA and BTH proved to be the best seed pretreatment inducers that reduced O. foetida infestation and increased plant growth and seed yield under field and controlled conditions. Induced tolerance was associated with reduced orobanche seed germination rate and tubercle number. Biological tolerance inducers reduced orobanche infestation under controlled conditions especially in quadratic plastic dishes but not under field conditions. In absence of complete resistance to broomrape, these results support the evidence of using tolerance inducers to control broomrapes and that could be considered as one additional component in an integrated control strategy.